Smart Tourism Ecosystems and Digital Job Creation in the Platform Economy Era: A Qualitative Study in Emerging Tourism Destinations - Nova Yudha Andriansyah Putra; Lia Mazia; Instianti Elyana (Pusat Riset dan Inovasi Nasional, 2026)
The accelerated growth of digital technologies has transformed the tourism industry into a highly interconnected and platform driven ecosystem. This study explores how smart tourism ecosystems contribute to digital job creation within the platform economy, particularly in emerging tourism destinations. While previous research has focused on technological adoption and tourist experience, limited attention has been given to employment generation and local economic inclusion. This study adopts a method qualitative approach using in-depth interviews, observations, and document analysis involving tourism stakeholders such as local entrepreneurs, digital platform workers, and community leaders. The findings reveal that smart tourism ecosystems characterized by ICT infrastructure, data integration, and stakeholder collaboration play a crucial role in enabling new forms of employment, including gig work, digital entrepreneurship, and content-based tourism promotion. Platforms such as Traveloka and Airbnb facilitate market access, reduce entry barriers, and create flexible job opportunities. However, challenges remain in terms of digital literacy, income stability, and platform dependency. This study was contributes of the literature by integrating smart tourism and digital labor perspectives and offers practical recommendations for policymakers and also stakeholders to foster inclusive and sustainable tourism development.